Risk factors for endometrial carcinoma among postmenopausal women in Sri Lanka: a case control study - Withanage Iresha udayangani Jayawickcrama; Chrishantha Abeysena (BMC, 2019)
Abstract Background Endometrial carcinoma burden is on the rise globally. The objective of this study was to determine the risk factors for endometrial carcinoma among postmenopausal women in Western province in Sri Lanka. Methods A case control study was conducted recruiting 83 incident cases of endometrial carcinoma and 332 unmatched hospital controls from all the secondary and tertiary care hospitals in the province using consecutive sampling technique. A case was defined as a postmenopausal woman who had been residing in the province for at least a period of 1 year, diagnosed to have endometrial carcinoma with histological confirmation within 3 months of the initiation of data collection of the study. Data were collected using validated interviewer administered questionnaire. Risk factor were identified through multiple logistic regression and results were expressed as adjusted odds ratios (AOR) and 95% confidence intervals (CI). Results The independent risk factors of endometrial carcinoma are having family history of any type of cancer among first degree relative (AOR = 12.6; 95% CI:5.14-30.9), generalized obesity (BMI ≥25 kg/m2) (AOR = 11.85; 95% CI:5.12-27.4), never conceived (AOR = 3.84; 95% CI:1.37-10.7), age at menarche ≤11 years (AOR = 4.07; 95% CI:1.16-14.2), age > 55 years (AOR = 4.69; 95% CI:2.16-10.2), monthly family income of ≤20,000 Rupees (AOR = 2.65; 95% CI:1.31-5.39), sub-optimal consumption of deep fried food (AOR = 0.17; 95% CI:0.06-0.46), and low level household activities (AOR = 2.82; 95% CI:1.34-5.92). Conclusions There were eight independent risk factors of endometrial carcinoma specific for Sri Lankan postmenopausal women identified. Some modifiable risk factors such as generalized obesity, sub-optimal dietary practices and low level physical activities need to be addressed at primary prevention level.